![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Find the value of $ \mu $ for which one root of the quadratic equation $ \mu {{\text{x}}^{\text{2}}} - {\text{14x}} + {\text{8 = 0}} $ is $ 6 $ times the other.
Answer
456.3k+ views
Hint: General form of quadratic equation is $ {\text{a}}{{\text{x}}^{\text{2}}} + {\text{bx}} + {\text{c}} = {\text{0}} $
If $ \alpha $ and $ \beta $ are the roots of the given quadratic equation, then
Sum of the roots of the equation is $ - \dfrac{{\text{b}}}{{\text{a}}} $
Product of the roots of the equation is $ \dfrac{{\text{c}}}{{\text{a}}} $
Follow the given conditions in the question and solve accordingly.
Complete step-by-step answer:
Given: The quadratic equation is $ \mu {{\text{x}}^{\text{2}}} - {\text{14x}} + {\text{8 = 0}} $
One root of the equation given is $ 6 $ times the other.
We need to find the value of $ \mu $
Let the roots of the given quadratic equation be $ \alpha $ and $ \beta $ respectively.
According to the question,
$ \alpha $ is 6 times of $ \beta $
$ \Rightarrow \alpha = 6 \times \beta $
Sum of the roots of the equation in general form $ {\text{a}}{{\text{x}}^{\text{2}}} + {\text{bx}} + {\text{c}} = {\text{0}} $ is $ - \dfrac{{\text{b}}}{{\text{a}}} $
Comparing the given equation $ \mu {{\text{x}}^{\text{2}}} - {\text{14x}} + {\text{8 = 0}} $ with the general form, we get
$
{\text{a}} = \mu \\
{\text{b}} = - 14 \\
{\text{c}} = 8 \;
$
$ \alpha + \beta = - \dfrac{{\text{b}}}{{\text{a}}} = - \left( {\dfrac{{ - {\text{14}}}}{\mu }} \right) $
$ \Rightarrow \alpha + \beta = \dfrac{{14}}{\mu } $ ……..Equation (1)
Given that $ \alpha = 6 \times \beta $
Substituting $ \alpha = 6 \times \beta $ in Equation (1)
We get,
$
{\text{6}}\beta + \beta = \dfrac{{{\text{14}}}}{\mu } \\
\Rightarrow {\text{7}}\beta = \dfrac{{{\text{14}}}}{\mu } \;
$
$ \Rightarrow \beta = \dfrac{2}{\mu } $ ……..Equation (2)
Product of the roots of the equation in general form $ {\text{a}}{{\text{x}}^{\text{2}}} + {\text{bx}} + {\text{c}} = {\text{0}} $ is $ \dfrac{{\text{c}}}{{\text{a}}} $
$ \alpha \times \beta = \dfrac{c}{a} = \dfrac{8}{\mu } $ ……..Equation (3)
Substituting $ \alpha = 6 \times \beta $ in Equation (3)
We get,
$ 6\beta \times \beta = \dfrac{8}{\mu } $
$ \Rightarrow 6{\beta ^2} = \dfrac{8}{\mu } $ ……..Equation (4)
Substituting Equation (2) in Equation (4) , we get
$
{\text{6}} \times {\left( {\dfrac{{\text{2}}}{\mu }} \right)^{\text{2}}} = \dfrac{{\text{8}}}{\mu } \\
\Rightarrow {\text{6}} \times \dfrac{{\text{4}}}{{{\mu ^{\text{2}}}}} = \dfrac{{\text{8}}}{\mu } \\
\Rightarrow \mu = 3 \;
$
Therefore, the value of $ \mu $ is $ 3 $ .
So, the correct answer is “3”.
Note: In this type of questions which involves the concept of quadratic equations, we need to have knowledge about the formulae related to sum of roots and product of roots of a general quadratic equation. Be careful with calculations as we come across many calculations. Follow the conditions given in the question and solve them accordingly to find the required answer.
If $ \alpha $ and $ \beta $ are the roots of the given quadratic equation, then
Sum of the roots of the equation is $ - \dfrac{{\text{b}}}{{\text{a}}} $
Product of the roots of the equation is $ \dfrac{{\text{c}}}{{\text{a}}} $
Follow the given conditions in the question and solve accordingly.
Complete step-by-step answer:
Given: The quadratic equation is $ \mu {{\text{x}}^{\text{2}}} - {\text{14x}} + {\text{8 = 0}} $
One root of the equation given is $ 6 $ times the other.
We need to find the value of $ \mu $
Let the roots of the given quadratic equation be $ \alpha $ and $ \beta $ respectively.
According to the question,
$ \alpha $ is 6 times of $ \beta $
$ \Rightarrow \alpha = 6 \times \beta $
Sum of the roots of the equation in general form $ {\text{a}}{{\text{x}}^{\text{2}}} + {\text{bx}} + {\text{c}} = {\text{0}} $ is $ - \dfrac{{\text{b}}}{{\text{a}}} $
Comparing the given equation $ \mu {{\text{x}}^{\text{2}}} - {\text{14x}} + {\text{8 = 0}} $ with the general form, we get
$
{\text{a}} = \mu \\
{\text{b}} = - 14 \\
{\text{c}} = 8 \;
$
$ \alpha + \beta = - \dfrac{{\text{b}}}{{\text{a}}} = - \left( {\dfrac{{ - {\text{14}}}}{\mu }} \right) $
$ \Rightarrow \alpha + \beta = \dfrac{{14}}{\mu } $ ……..Equation (1)
Given that $ \alpha = 6 \times \beta $
Substituting $ \alpha = 6 \times \beta $ in Equation (1)
We get,
$
{\text{6}}\beta + \beta = \dfrac{{{\text{14}}}}{\mu } \\
\Rightarrow {\text{7}}\beta = \dfrac{{{\text{14}}}}{\mu } \;
$
$ \Rightarrow \beta = \dfrac{2}{\mu } $ ……..Equation (2)
Product of the roots of the equation in general form $ {\text{a}}{{\text{x}}^{\text{2}}} + {\text{bx}} + {\text{c}} = {\text{0}} $ is $ \dfrac{{\text{c}}}{{\text{a}}} $
$ \alpha \times \beta = \dfrac{c}{a} = \dfrac{8}{\mu } $ ……..Equation (3)
Substituting $ \alpha = 6 \times \beta $ in Equation (3)
We get,
$ 6\beta \times \beta = \dfrac{8}{\mu } $
$ \Rightarrow 6{\beta ^2} = \dfrac{8}{\mu } $ ……..Equation (4)
Substituting Equation (2) in Equation (4) , we get
$
{\text{6}} \times {\left( {\dfrac{{\text{2}}}{\mu }} \right)^{\text{2}}} = \dfrac{{\text{8}}}{\mu } \\
\Rightarrow {\text{6}} \times \dfrac{{\text{4}}}{{{\mu ^{\text{2}}}}} = \dfrac{{\text{8}}}{\mu } \\
\Rightarrow \mu = 3 \;
$
Therefore, the value of $ \mu $ is $ 3 $ .
So, the correct answer is “3”.
Note: In this type of questions which involves the concept of quadratic equations, we need to have knowledge about the formulae related to sum of roots and product of roots of a general quadratic equation. Be careful with calculations as we come across many calculations. Follow the conditions given in the question and solve them accordingly to find the required answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Find the value of x if the mode of the following data class 11 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you graph the function fx 4x class 9 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Name the states which share their boundary with Indias class 9 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Difference Between Plant Cell and Animal Cell
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is pollution? How many types of pollution? Define it
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.
![arrow-right](/cdn/images/seo-templates/arrow-right.png)